A novel DNA tetrahedron–hairpin probe for in situ "off–on" fluorescence imaging of intracellular telomerase activity. Issue 8 (16th March 2016) - Feng, Qiu-Mei; Zhu, Meng-Jiao; Zhang, Ting-Ting; Xu, Jing-Juan; Chen, Hong-Yuan
Abstract : A DNA tetrahedron–hairpin probe with a high recovery efficiency is designed for in situ fluorescence imaging of intracellular telomerase activity. Abstract : A novel three-dimensionally structured DNA probe is reported to realize in situ "off–on" imaging of intracellular telomerase activity. The probe consists of a DNA tetrahedron and a hairpin DNA on one of the vertices of the DNA tetrahedron. It is composed of four modified DNA segments: S1–Au nanoparticle (NP) inserting a telomerase strand primer (TSP) and S2–S4, three Cy5 dye modified DNA segments. Fluorescence of Cy5 at three vertices of the DNA tetrahedron is quenched by the Au NP at the other vertex due to the effective fluorescence resonance energy transfer (FRET) ("off" state). When the probe meets telomerase, the hairpin structure changes to rod-like through complementary hybridization with the telomerase-triggered stem elongation product, resulting in a large distance between the Au NP and Cy5 and the recovery of Cy5 fluorescence ("on" state). The molar ratio of 3 : 1 between the reporter (Cy5) and the target related TSP makes the probe show high sensitivity and recovery efficiency of Cy5 in the presence of telomerase extracted from HeLa cells. Given the functional and compact nanostructure, the mechanically stable and noncytotoxic nature of the DNA tetrahedron, this FRET-based probe provides more opportunities for biosensing, molecular imaging and drug delivery.